A Cross Sectional Study to Evaluate The Existence of Drop in “Core Body Temperature” of Afebrile Arabic Iraqi Citizens Who are Living Inside Iraq, Applied Study in Private Clinic in Baghdad – Iraq - Ali Mohammed Fadhil; Yousif Jawad Kadom (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Normal average core body temperature had been established at 37 ºC since nineteenth century. However, recently many researchers point to a decrease in the average normal human body temperature, bellow this level, in certain communities.Methodology: A cross sectional study involved 504 individuals been conducted in private clinics, in Baghdad - Iraq, over period extended from 7 11 2020 - 30 12 2020.Objective: to show if there is a drop in human core body temperature in Iraq or not.Results: human core body temperature drop, in Iraq, bellow standard levels.